PENGARUH KARAKTERISTIK WIRAUSAHA DAN PEMBERIAN DANA BERGULIR TERHADAP KINERJA UMKM - Winda Ardiani; Rizki Putra (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2019)
The role of SMEs in the city of Deli Serdang considered very important especially in the field of SMEs is a lot of employment, for that UMKM activities should be driven improvement in business performance. This study uses a quantitative descriptive approach that describes the influence of variable characteristics of entrepreneurship and grant of revolving fund to the performance of SMEs. This research was conducted in Denai Lama Village of Deli Serdang Regency with 100 UMKM respondents who have received revolving fund. The results showed that there is a significant effect of entrepreneurial characteristics p = 0,000 0,005 and Revolving Loan Fund p = 0,003 0,005 simultaneously to Entrepreneurial Performance. Of the two variables, the variables of entrepreneurial characteristics are the most influential variable compared to the revolving fund lending variable. Entrepreneurship should improve communication with employees in developing business runs so that employees feel they have a business so they can improve their personal performance. The government as a channeling fund distributor should provide training and intensive assistance to SMEs in order to utilize the revolving fund is really appropriate allocation for the progress of SME business. Keywords — Entrepreneurial Characteristics, Revolving Fund, UMKM Performance.